(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2020)
The banana tree is a tropical fruit plant, grown commercially throughout Brazil. It’s commonly found of coastal regions, the banana has been gaining space in the Paulista Plateau, mainly in the midwest region of the state. The objective of this work was to evaluate the interference of microaspersion irrigation in the vegetative and productive characteristics of three banana genotypes in three production cycles, cultivated under the edaphoclimatic conditions of the municipality of Vera Cruz in São Paulo state. The planting was carried out in December 2015, with micropropagated and acclimated seedlings. The statistical design adopted was randomized blocks, with 6 treatments, in a 3 x 2 factorial arrangement with 3 genotypes and 2 cultivation environments (irrigated and non irrigated). The genotypes evaluated were: BRS Princesa (Maçã subgroup), Galil 18 (Prata subgroup) and Grande Naine (Cavendish subgroup). Vegetative variables (plant height, pseudostem circumference and the number of live leaves in flowering); production variables (clusters and weight mass, productivity, number of hands per bunches and number of fruit for hands) and fruit quality (diameter, shell thickness and length), were evaluated. It is concluded that the irrigation localized by microaspersion positively interfered in the plant performance, improving the vegetative and productive characteristics of the BRS Princesa (Maçã subgroup), Galil 18 (Prata subgroup) and Grande Naine (Cavendish subgroup) genotypes, in Vera Cruz, midwest region of São Paulo state.